Pulsing blue light through closed eyelids: effects on acute melatonin suppression and phase shifting of dim light melatonin onset - Figueiro, Mariana G (Nat Sci Sleep, 2014)
Circadian rhythm disturbances parallel the increased prevalence of sleep disorders in older adults. Light therapies that specifically target regulation of the circadian system in principle could be used to treat sleep disorders in this population. Current recommendations for light treatment require the patients to sit in front of a bright light box for at least 1 hour daily, perhaps limiting their willingness to comply. Light applied through closed eyelids during sleep might not only be efficacious for changing circadian phase but also lead to better compliance because patients would receive light treatment while sleeping. Reported here are the results of two studies investigating the impact of a train of 480 nm (blue) light pulses presented to the retina through closed eyelids on melatonin suppression (laboratory study) and on delaying circadian phase (field study). Both studies employed a sleep mask that provided narrowband blue light pulses of 2-second duration every 30 seconds from arrays of light-emitting diodes. The results of the laboratory study demonstrated that the blue light pulses significantly suppressed melatonin by an amount similar to that previously shown in the same protocol at half the frequency (ie, one 2-second pulse every minute for 1 hour). The results of the field study demonstrated that blue light pulses given early in the sleep episode significantly delayed circadian phase in older adults; these results are the first to demonstrate the efficacy and practicality of light treatment by a sleep mask aimed at adjusting circadian phase in a home setting.